8‐Oxoguanine DNA glycosylase modulates the cell transformation process in pulmonary fibrosis by inhibiting Smad2/3 and interacting with Smad7. Issue 10 (17th August 2020) - Wang, Yahong; Chen, Ting; Pan, Zhanchun; Lin, Ziying; Yang, Lawei; Zou, Baoan; Yao, Weimin; Feng, Dehui; Huangfu, Changmei; Lin, Chunyu; Wu, Guiqing; Ling, Huayu; et al.
Abstract: The DNA repair enzyme 8‐oxoguanine DNA glycosylase‐1 (OGG1) is involved in early embryonic development, as well as in multiple conditions, including cardiac fibrosis, diabetes, and neurodegenerative diseases. But, function of OGG1 in pulmonary fibrosis was not entirely clear. In this study, we identified a novel function of OGG1 in the cell transformation process in pulmonary fibrosis. We demonstrated that OGG1 and Smad7 co‐localize and interact in A549 cells. Bleomycin‐induced pulmonary fibrosis was established in wild‐type (WT) and Ogg1 ‐/‐ mice. Upon treatment with transforming growth factor (TGF)‐β1, increased OGG1 expression was observed in WT mice with pulmonary fibrosis as well as in A549 cells, MRC‐5 cells, and primary rat type II alveolar epithelial cells. The increased expression of OGG1 promoted cell migration, while OGG1 depletion decreased migration ability. Expression of the transformation‐associated markers vimentin and alpha‐smooth muscle actin were also affected by OGG1. We also observed that OGG1 promoted TGF‐β1‐induced cell transformation and activated Smad2/3 by interacting with Smad7. The interaction between OGG1 and the TGF‐β/Smad axis modulates the cell transformation process in lung epithelial cells and fibroblasts. Moreover, we demonstrated that Ogg1 deficiency relieved pulmonary fibrosis in bleomycin‐treated mice. Ogg1 knockout decreased the bleomycin‐induced expression of Smad7 and phosphorylation of Smad2/3 in mice. These findings suggest that OGG1 has multiple biological functions in the pathogenesis of pulmonary fibrosis.